The Andreasson affair : the true story of a close encounter of the fourth kind - Fowler, Raymond E., 1933- (New Page Books, a division of The Career Press, Inc., 2015)
"The classic case of alien abduction rereleased with a new afterword for a new generation"--Page 4 of cover